A comparison of routine and case-managed pathways for recovery from musculoskeletal disorders in people in employment. Issue 17 (14th August 2022) - Bergman, Beverly P.; Demou, Evangelia; Lewsey, James; Macdonald, Ewan
Abstract: Purpose: To compare outcomes in employed people from an enhanced routine management pathway for musculoskeletal disorders within National Health Service Scotland with an existing active case-management system, Working Health Services Scotland. Materials and methods: The study comprised a service evaluation using anonymised routinely collected data from all currently employed callers presenting with musculoskeletal disorder to the two services. Baseline demographic and clinical data were collected. EuroQol EQ-5D TM scores at the start and end of treatment were compared for both groups, overall and by age, sex, socio-economic status, and anatomical site, and the impact of mental health status at baseline was evaluated. Results: Active case-management resulted in greater improvement than enhanced routine care. Case-managed service users entered the programme earlier in the recovery pathway; there was evidence of spontaneous improvement during the longer waiting time of routine service clients but only if they had good baseline mental health. Those most disadvantaged through mental health co-morbidity showed the greatest benefit. Conclusions: People with musculoskeletal disorders who have poor baseline mental health status derive greatest benefit from active case-management. Case-management therefore contributes to reducing health inequalities and can help to minimise long-term sickness absence. Shorter waiting times contributed to better outcomes in the case-managed service. Implications for Rehabilitation: Musculoskeletal disorders are a major cause of inability to work. Case-management is effective in helping people with musculoskeletal disorders to return to work. People who have the poorest mental health are likely to gain the greatest benefit from case-management of their musculoskeletal disorders.